'Prole Art Threat': The Fall, the Blue Orchids and the politics of the post-punk working-class autodidact. (1st April 2014) - Wilkinson, David
In much of the writing that exists on The Fall, a persistent myth is perpetuated of the inscrutable character of Mark E. Smith. One of the contributing factors to this myth concerns Smith's politics, commonly seen as ambiguous yet so far not analysed in detail. Here I shed some light on this issue. Furthermore, I wish to open up academic discussion on the work of The Blue Orchids, an outgrowth of The Fall, which developed an outlook inchoate in the original line-up, one which was lost when Smith became its driving force. There is a fascinating comparison to be made between the Fall and Blue Orchids on the basis of working-class negotiations of leftist post-punk at the dawn of Thatcherism. I examine how the two bands' cultural production and political attitudes towards freedom and pleasure were shaped by residual countercultural and class-based influences. I then consider the divergent outcomes of Smith's affinities with Thatcherism (which nevertheless retained oppositional elements) and The Blue Orchids' mystical rejection of both the New Right and New Pop in favour of an oppositional ethos of fulfilment that was part G. I. Gurdjieff and part Worker's Educational Association.